Generalised dissipative asynchronous output feedback control for Markov jump repeated scalar non‐linear systems with time‐varying delay. Issue 13 (4th July 2019) - Wang, Jing; Huo, Shicheng; Xia, Jianwei; Park, Ju H.; Huang, Xia; Shen, Hao
Abstract : This work strives for the issue of generalised dissipative asynchronous output feedback control for Markov jump repeated scalar non‐linear systems with time‐varying delay. The objective is to design an asynchronous output feedback controller, which ensures that the closed‐loop system is generalised stochastically dissipative. Meanwhile, such an asynchronous controller covers not only the asynchronous controller but also the mode‐independent one. By means of a stochastic analysis technique and a modified matrix decoupling method, sufficient conditions are given for deriving the desired controller. At length, an illustrative example is provided to demonstrate the availability of the presented approach.